2006
DOI: 10.1073/pnas.0507165103
|View full text |Cite
|
Sign up to set email alerts
|

Pollination decays in biodiversity hotspots

Abstract: As pollinators decline globally, competition for their services is expected to intensify, and this antagonism may be most severe where the number of plant species is the greatest. Using metaanalysis and comparative phylogenetic analysis, we provide a global-scale test of whether reproduction becomes more limited by pollen receipt (pollen limitation) as the number of coexisting plant species increases. As predicted, we find a significant positive relationship between pollen limitation and species richness. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
226
3
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(258 citation statements)
references
References 37 publications
(42 reference statements)
16
226
3
8
Order By: Relevance
“…In this context, Vamosi et al (2006) found that global 'hotspots' of angiosperm diversity also tend to be areas of common PL. They interpreted this association as an ecological consequence of heightened competition for pollinators (see also Armbruster & Muchhala 2009).…”
Section: Pollen Limitation and Plant Diversificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Vamosi et al (2006) found that global 'hotspots' of angiosperm diversity also tend to be areas of common PL. They interpreted this association as an ecological consequence of heightened competition for pollinators (see also Armbruster & Muchhala 2009).…”
Section: Pollen Limitation and Plant Diversificationmentioning
confidence: 99%
“…Even when supplementation indicates PL during a single flowering season, iteroparous species may not suffer lifetime limitation, which is most relevant for population dynamics and natural selection, because elevated reproductive effort stimulated by supplementation during one flowering season typically reduces a plant's seed production during subsequent seasons . Finally, the populations and species for which published results of pollen supplementation experiments are available may not be representative because of unequal geographic and taxonomic sampling (Vamosi et al 2006) and a publication bias favouring statistically significant responses . Given the preceding problems, the finding that roughly 60 per cent of pollen supplementation experiments significantly elevate seed production (Larson & Barrett 2000;Knight et al 2005a) must overestimate the general incidence of PL; however, it still suggests that incomplete ovule fertilization compromises seed production by many plants.…”
Section: How Common Is Pollen Limitation and When Does It Matter?mentioning
confidence: 99%
“…Recent genetic studies on other birdpollinated plants in the SWAFR have demonstrated an impact on the mating system, with increased selfing and increased correlated paternity associated with reduced population size following habitat fragmentation . Introduced, non-native pollinators such as European honeybees (A. mellifera), and increased competition for declining vertebrate pollinators, strongest in biodiversity hotspots (Vamosi et al, 2006), affect pollen limitation and seed set in many species with already low conversions of flowers to fruits (Ayre and Whelan, 1989;England et al, 2001), increasing extinction risk. Our results highlight the additional conservation genetic concerns from bird-pollinator disruption that may result in a significant increase in near-neighbour pollen dispersal, correlated paternity and inbreeding through bi-parental mating.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…Functional diversity responds differently to changes in land use and management than other measures, particularly the traditional ones showing that conserving other diversity components (such as species number or abundance) will not necessarily conserve functional diversity (Bennett et al, 2014;Katovai et al, 2012;Van Capelle et al, 2012). In some cases measures of functional diversity or trait-based approach responded more precisely than other measures (Dengler et al, 2014;Pelosi et al, 2014), suggesting that this approach can potentially better predict the impacts, although other corroborative studies are needed.…”
Section: Discussionmentioning
confidence: 94%
“…As most part of Europe lies in the northern temperate climate zone, current conclusions and recommendations regarding functional diversity and conservation tend to be less suitable to ecosystems from outside that climate. Because tropical species communities are prone to be more complex (Janzen, 1975;Vamosi et al, 2006), relationships between ecosystem functioning and functional diversity in the tropics may not be as straightforward, as is usually assumed (Freitas et al, 2012;Martins and Batalha, 2006). Testing hypothesis in tropical ecosystems would contribute to expanding the current understanding of functional diversity in conservation strategies' applicability.…”
Section: Discussionmentioning
confidence: 99%